2016
DOI: 10.1080/23294515.2016.1156188
|View full text |Cite
|
Sign up to set email alerts
|

Alternative consent models for comparative effectiveness studies: Views of patients from two institutions

Abstract: Background: Informed consent requirements generally require a lengthy process and signed documentation for patients to participate in clinical research. With growing interest in comparative effectiveness research (CER), whereby patients receive approved (nonexperimental) medicines for their medical condition, questions have been raised whether the same consent requirements should apply. Little input from patients has been part of these debates. Methods: We conducted two "deliberative engagement sessions" with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…Our study found stronger support for General Approval in prospective observational studies than did prior surveys with patients or the general public . For example, while over two‐thirds of this multi‐stakeholder group supported General Approval for an observational hypertension study following deliberation, only half of participants in an earlier patient‐only DES did so .…”
Section: Discussionmentioning
confidence: 42%
“…Our study found stronger support for General Approval in prospective observational studies than did prior surveys with patients or the general public . For example, while over two‐thirds of this multi‐stakeholder group supported General Approval for an observational hypertension study following deliberation, only half of participants in an earlier patient‐only DES did so .…”
Section: Discussionmentioning
confidence: 42%
“…39 Such public preferences may not be fixed: the same study noted a significant increase in participants' willingness to accept an RWOC approach after a period of deliberation on the topic. 39 The finding that almost all participants wanted to be asked for informed consent even for retrospective research further highlights the challenges in reconciling public opinion with policy. Nonetheless, these results suggest that RWOC designs cannot simply consider the material risk to patients but must also address a widespread desire for individuals to be informed and give consent.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41] In a case where most participants initially rejected RWOC, they were more accepting of a streamlined consent. 39 Such public preferences may not be fixed: the same study noted a significant increase in participants' willingness to accept an RWOC approach after a period of deliberation on the topic. 39 The finding that almost all participants wanted to be asked for informed consent even for retrospective research further highlights the challenges in reconciling public opinion with policy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is a growing body of literature regarding the ethical and regulatory challenges associated with fielding PCTs in the USA [3] and some empirical work examining patients' perspectives on pragmatic research conducted in usual care settings in the USA [8][9][10], comparatively little attention has focused on physicians' attitudes toward such research. A 2009 study found that while more than half of the physicians surveyed believed CER would improve clinical care, 65% thought it would restrict physicians' practices [11].…”
mentioning
confidence: 99%